Validity and reliability test of parent's satisfaction in children with closed totally displaced supracondylar humeral fracture. - Kamolporn Kaewpornsawan (2018)
OBJECTIVE: To construct a questionnaire with validity and reliability test of the parents' satisfaction in children with closed totally displaced supracondylar humeral fractures and to compare the satisfaction score between group A, closed reduction and pinning and group B,open reduction and pinning. MATERIAL AND METHOD: The questionnaire was developed in 19 items 5 dimensions 1. The deformity 2. The doctor and nursing care 3. The cosmetic results 4. The range of motion of the elbow 5. The complications. The content validity was approved by 5 experts. In item score. From 1996 to 2004, the parents of the children with fractures were included.Sixteen parents gave the satisfaction score 2 times by 1 month interval after 6 months from the initial injuries. Nine parents were in group A and 7 parents were in group B. The reliability test by Cronbach's alpha was done. The satisfaction score was compared between group A and group B. RESULTS: The average item score was 0.86 (0.6-1). The Cronbach's alpha was 0.6482 in group A and 0.8037 in group B. The mean parents satisfaction score were 81.4 in group A and 70.0 in group B with statistical significant difference (P = 0.008). CONCLUSION: The questionnaire had good validity and reliability and could be helpful in decision making for the choice of the treatment. The closed reduction should be done first from the parent's point of view.